OD TRIVIJALIZACIJE MEDIJSKIH SADRŽAJA DO UVOĐENJA ČLANKA SRAMOĆENJA U KAZNENI ZAKON – JESU LI HRVATSKI MEDIJI NA PROFESIONALNOJ PREKRETNICI? (Philological Studies, 2019)
Inscribing of Article 148.1 called „embarrassment“ in to the Criminal Code is an additional attack on media freedom because every journalist who present "factual assertion" that can harm one's honor and reputation shall be fined. Is the "factual assertion" substantial for public interest, in its sole discretion determines the subject judge. This article was adopted "in order to put an end to the press" Vladimir Šeks told to the media (Lovrić, 2011), what confirms the political pressure on media practice in Croatia. When we talk about media rights and freedoms, for the first time reversing four years of legislative changes were made at the expense of media freedom, which in twenty-four years of democracy in Croatia did not happened. Any change in the law was a step forward in expanding media freedom, and this is actually the first regression in that sense. Croatian Journalists' Association warned that the truth can not be penalized in any way, but the problem in the Croatian media lies much deeper - in Croatia there is no newspapers that deals with serious information. Every day we witness the trivialisation of media content but consumers of media content want quality information, they want it on time and want it for a reason. In further work, we will try to answer the question whether there is in Croatia sufficiently serious newspaper or media outlet that would clearly separate information from rumors and tabloid content through deeper interview with professor dr.sc Gordana Vilović where she said: "No, no! And that's the saddest part of Croatian journalism because in our country was born one semiform of semitabloids." In addition, in the work we ask the question of whether this form of journalism cause the introduction of Article 148. of the Criminal Code, and what is the character of the media in Croatia. Does Croatian journalism rests on hearsay, in a semi-structured interview responds dr. sc. Gordan Vilovic2 . How vocational journalists association acts in the new situation, in unstructured interview we have talked to Ana Raić - Knezević3 . Vesna Alaburić4 , in structured interview, talks about how the legal profession interprets the consequences of the introduction of Article of humiliation. Through the work, in the content analysis method, we will try to give the answer is Croatian media space at a turning point and what is the future of Croatian media.
Keywords: gossip, tabloidization, embarrassment, legal regulations, the future of media